Property Analysis of Carbon Fiber with Vinyl Ester Resin Type Sizing Agent - Ding, Wanwan; Chen, Juan; Liu, Jianye; Pang, Zengkai; Guan, Ruifang (Asian Journal of Chemistry, 2013)
The influences of vinyl ester resin type sizing agent on the properties of carbon fiber and composite were studied. The yarn abrader, X-ray photoelectron spectroscopy were used to characterize wear resistance and chemical element of carbon fiber. Interlaminar shear strength of composite was tested by universal testing machine. The results indicated that wear resistance of sized carbon fiber was significantly improved. X-Ray photoelectron spectroscopy results demonstrated that the activated function groups of sized carbon fiber were more than desized one. The interfacial adhesion of sized carbon fiber/vinyl ester resin (CF/VE) composite was strengthened and interlaminar shear strength of sized carbon fiber/vinyl ester resin composite reached 45.9 MPa.